Mitochondrial-Targeting Anticancer Agent Conjugates and Nanocarrier Systems for Cancer Treatment - Battogtokh, Gantumur; Cho, Yong-Yeon; Lee, Joo Young; Lee, Hye Suk; Kang, Han Chang (Frontiers in Pharmacology, 2018)
The mitochondrion is an important intracellular organelle for drug targeting due to its key roles and functions in cellular proliferation and death. In the last few decades, several studies have revealed mitochondrial functions, attracting the focus of many researchers to work in this field over nuclear targeting. Mitochondrial targeting was initiated in 1995 with a triphenylphosphonium-thiobutyl conjugate as an antioxidant agent. The major driving force for mitochondrial targeting in cancer cells is the higher mitochondrial membrane potential compared with that of the cytosol, which allows some molecules to selectively target mitochondria. In this review, we discuss mitochondria-targeting ligand-conjugated anticancer agents and their in vitro and in vivo behaviors. In addition, we describe a mitochondria-targeting nanocarrier system for anticancer drug delivery. As previously reported, several agents have been known to have mitochondrial targeting potential; however, they are not sufficient for direct application for cancer therapy. Thus, many studies have focused on direct conjugation of targeting ligands to therapeutic agents to improve their efficacy. There are many variables for optimal mitochondria-targeted agent development, such as choosing a correct targeting ligand and linker. However, using the nanocarrier system could solve some issues related to solubility and selectivity. Thus, this review focuses on mitochondria-targeting drug conjugates and mitochondria-targeted nanocarrier systems for anticancer agent delivery.